2010
DOI: 10.5021/ad.2010.22.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Chromoblastomycosis Caused byPhialophora richardsiae

Abstract: Chromoblastomycosis is a chronic fungal disease of the skin and subcutaneous tissues caused by a group of dematiaceous (black) fungi. The most common etiologic agents are Fonsecaea pedrosoi and Cladophialophora carrionii, both of which can be isolated from plant debris. The infection usually follows traumatic inoculation by a penetrating thorn or splinter wound. Several months after the injury, painless papules or nodules appear on the affected area; these papules then progress to scaly and verrucose plaques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Pseudoepitheliomatous hyperplasia with hyperkeratosis and parakeratosis and sclerotic bodies are seen on histopathology (1,5). One case of P richardisae presenting in this way was recently reported (6). Eumycotic mycetomas are midway in the spectrum of disease between phaeohyphomycosis and chromoblastomycosis.…”
Section: Diagnosismentioning
confidence: 92%
“…Pseudoepitheliomatous hyperplasia with hyperkeratosis and parakeratosis and sclerotic bodies are seen on histopathology (1,5). One case of P richardisae presenting in this way was recently reported (6). Eumycotic mycetomas are midway in the spectrum of disease between phaeohyphomycosis and chromoblastomycosis.…”
Section: Diagnosismentioning
confidence: 92%
“…2 Cases of chromoblastomycosis typically presented with subcutaneous verrucous, ulcerated, or crusted lesions and eumycotic mycetoma, which are tumor-like lesions with draining sinus tracts and fungal grains that are caused by P richardsiae. 3,9 Subcutaneous P richardsiae infections can occur in healthy people and in people with immunocompromised conditions, such as those having diabetes mellitus, having posttransplantation status, taking immunosuppression therapy, or taking chemotherapy. 3,10 Invasive infections caused by P richardsiae were usually observed in immunocompromised patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A case of disseminated Phaeohyphomycosis because of Exophiala spinifera during pregnancy was reported by Ricardo et al, and a case of concurrent mycetoma and chromoblastomycosis was reported by Murthy et al, but a mycetoma‐like presentation of chromoblastomycosis is yet to be reported. It is said that chromoblastomycosis and pheohyphomycosis represent two poles of a spectrum of disease caused by pigmented fungi . So, we assume that the spectrum of diseases caused by dematiaceous fungi has no strict boundries, and a mycetoma‐like presentation may be induced by F. pedrosoi during immunosuppression.…”
Section: Discussionmentioning
confidence: 99%